Preparation and characterization of cefuroxime axetil solid dispersions using poloxamer 188 - Thaeer Sankari; Sahar Al-Hariri (Universidade de São Paulo, 2019)
The main objective of the present work was to enhance the solubility and dissolution rate of poorly water-soluble drug cefuroxime axetil (CA) by formulating it into solid dispersions (SDs) with water soluble carrier poloxamer 188. Different methods were employed to prepare the dispersion, such as: Solvent method (SM), Kneading method (KM), Melt evaporation method (MEM) and Physical mixture (PM) in different drug: carrier ratios 1:1, 1:2 and 1:3 (cefuroxime axetil: poloxamer 188). The physical mixture(s) and solid dispersion(s) were characterized for drug carrier interaction, drug content, solubility, dissolution rate, differential scanning calorimetry (DSC) and FT-IR study. The dissolution rate of the prepared solid dispersion systems was determined in phosphate buffer (pH 6.8) for 1 h. The solubility of drug from different systems was also determined in water. All SD formulations were found to have a higher dissolution rate comparatively to pure CA. The dissolution rate was enhanced in the following order SM > MEM > KM. The enhancement of dissolution rate may be caused by increase wettability, dispersibillity reduction in particle size or the formation of CA β crystalline. The FT-IR study probability revealed that there was no chemical interaction between drug and poloxamer 188.